Traumatic Optic Neuropaty - Risha Feby Amelia, Baiq; Aulya Amy Aprilia, Noer; Febriya Moestafa, Rizka (Jurnal KESANS : Kesehatan dan Sains, 2022)
TON or traumatic optic neuropathy is a condition that can cause blindness which can be caused by trauma to the orbital area or head trauma. In its classification, TON is divided into two, namely direct and indirect. Direct TON or direct TON, is usually caused by a decrease or loss of a person's visual ability and the chance of recovery is smaller than indirect TON. This direct TON usually occurs when the optic nerve is laced with surrounding bone or the cause can be anatomical structural abnormalities. TON treatment can be done in two ways (1) Treatment with high doses of corticosteroids (2) with surgery.